Analisis Akuntabilitas Kinerja Kantor Wilayah Badan Pertanahan Nasional Provinsi Sumatera Utara - Apriliani, Diza; Wibowo, Muhammad Rizaldy (ARBITRASE: Journal of Economics and Accounting, 2022)
This research aims to find out the problems that occur in performance accountability at the Regional Office of the National Land Agency of North Sumatra Province as well as solutions to the problems that occur. The research method used in this research is qualitative with a case study approach using primary data and secondary data. The data collection techniques used are through interviews and documentation. The results showed that there are problems in the performance reporting and performance achievement components, namely there are still elements that have not been met in the format of preparing performance reports based on PermenPAN RB no. 53 of 2014, there is no monitoring of outcomes as a follow-up to the achievement of performance targets (output). As well as the access of SAKIP data is still not transparency because there has been no publication of documents on the performance accountability system of government agencies (SAKIP) in the official website of the National Land Agency of North Sumatra province